PENERAPAN FRAMEWORK ITIL V3 DALAM ANALISIS TATA KELOLA SISTEM INFORMASI LAYANAN AKADEMIK DOMAIN SERVICE TRANSITION - I Putu Ramayasa (LPPM Universitas Dhyana Pura, 2020)
ABSTRACTOne of the organization that utilizes information technology is university. The application of information technology at university is very useful if it runs in accordance with the goals, vision and mission of the organization. STIKOM Bali is one of the university in Bali that utilizes information technology in its organizational activities. In the application of information technology, it is necessary to plan related steps to be taken as well as good strategy management. This can improve service quality, operational effectiveness and budget efficiency without reducing quality. Information technology based services at STIKOM Bali are academic information system. The use of this information system does not necessarily run effectively and efficiently. Need for an adjustment process from both stakeholders and students who use the information system. A study is needed to measure the level of maturity and success in the use of information technology compared to manuals. This measurement is carried out to find out how much the readiness of users in migrating from manual to information systems, whether there are guidelines for the addition of information technology services, service configuration management, and guidelines for dealing with problems and risks. In this reserach, the analysis of information system uses the framework of Information Technology Infrastructure Library (ITIL) version 3 on the domain service transition. The results of this study are in the form of the expected maturity level value in accordance with the results of the questionnaire and the value of the current maturity level based on the results of interviews and observations as well as recommendations for improvement and improvement that must be done.Keywords: IT Governance, Academic Information System, ITIL V3, Domain Service transition.ABSTRAKSalah satu organisasi yang memanfaatkan teknologi informasi adalah perguruan tinggi. Penerapan teknologi informasi pada perguruan tinggi ini sangatlah bermanfaat apabila berjalan sesuai dengan tujuan, visi dan misi organisasi. STIKOM Bali merupakan salah satu perguruan tinggi di Bali yang memanfaatkan teknologi informasi dalam kegiatan organisasinya. Dalam penerapan teknologi informasi perlu adanya perencanaan terkait langkah-langkah yang harus diambil serta manajemen strategi yang baik. Hal ini dapat meningkatkan kualitas layanan, efektifitas operasional dan efisiensi anggaran tanpa mengurangi kualitas. Layanan yang berbasis teknologi informasi pada STIKOM Bali adalah layanan akademik. Pemanfaatan sistem informasi ini tidak serta merta nerjalan dengan efektif dan efisien. Perlunya proses penyesuaian baik dari pihak stakeholder maupun mahasiswa yang menggunakan sistem informasi tersebut. Perlu adanya kajian untuk mengukur tingkat kematangan dan keberhasilan dalam pemanfaatan teknologi informasi ini dibandingkan manual. Pengukuran ini dilakukan untuk mengetahui seberapa besar kesiapan pengguna dalam migrasi dari manual ke sistem informasi, apakah terdapat pedoman untuk penambahan layanan teknologi informasi, manajemen konfigurasi layanan, dan pedoman untuk menghadapi permasalahan dan resiko. Pada penelitian ini analisa tata kelola sistem informasi menggunakan framework kerja Information Technology Infrastructure Library (ITIL) versi 3 pada domain service transition. Hasil dari penelitian ini berupa nilai maturity level yang diharapkan sesuai dengan hasil kuisioner dan nilai current maturity level berdasarkan hasil wawancara dan observasi serta rekomendasi perbaikan dan peningkatan yang harus dilakukan.Kata Kunci: Tata Kelola IT, Layanan Akademik, ITIL V3, Domain Service transition.